STRATEGI PENGEMBANGAN DESA TERTINGGAL DI NAGARI BATU BANYAK KECAMATAN LEMBANG JAYA KABUPATEN SOLOK (JURNAL SPASIAL, 2014)
Nagari Batu Banyak is one of the villages in West Sumatra. Weak physical and non-physical potential is thought to be a trigger lagging rural villages. For the purpose of this research is to determine the development strategy of backward villages in order to become a developed country. Qualitative research methods FGD (Focus Group Discussion) involving community leaders, cadiak pandai, and Wali Nagari. To reinforce the data, the researchers also conducted observations and interviews with informants. Appointment done by using purposive sampling while to determine rural development strategy using SWOT analysis (Strengths / strength, Weakness / weakness, Opportunities / opportunities, and Threats / threats) .Next, data analysis techniques through reduction, display, classification, and the conclusion. The result showed that the Nagari Batu Banyak an agricultural area with development potential persawahan.Belum type of physical and non-physical villages villages hamper progress. It can be seen from the acquisition of land resources are limited, damaged irrigation, and low production road access. While human resources, social institutions and economic institutions are still weak due to mental and public instant culture. Therefore, the strategy of rural development can be done by improving and optimizing natural resources through the use of quality seeds, improved irrigation and access roads production, improve the way the process of agriculture, improve human resources by training and counseling, socialization of economic action immoral, to improve the economy through the eyes of search Alternatively, set up a village granary, and to enhance community participation through social institutions.Keywords: strategy, strategy development, backward village